Book Reviews - Pilli, Einike (Journal of European Baptist Studies, 2025)
Mark Stirling and Mark Meynell (eds), Not So with You: Power and Leadership for the Church (Wipf & Stock, 2023). ISBN: 9781666760163 Wendy J. Porter, Worship, Music and Interpretation: Exploratory Essays. McMaster General Studies Series (Pickwick Publications, 2024). ISBN: 9798385223305 Carlo Calleja, Communities of Kinship: Retrieving Christian Practices of Solidarity with Lepers as a Paradigm for Overcoming Exclusion of Older People (Lexington Books/Fortress Academic, 2024). ISBN: 9781978711976 Teun van der Leer, Looking in the Other Direction: The Story of the Believers Church Conferences. Amsterdam Series in Baptist and Mennonite Theologies (Pickwick Publications, 2023). ISBN: 9781666766790 J. August Higgins, The Crisis of Conversion: Reimagining Religious Experience for a Postmodern Evangelical Spirituality. Amsterdam Series in Baptist and Mennonite Theologies (Pickwick Publications, 2024). ISBN: 9798385204618 Klaus Koschorke, A Short History of Christianity Beyond the West: Asia, Africa, and Latin America 1450–2000 (Brill, 2025). ISBN: 9789004699823 Pontien Ndagijimana Batibuka, Baptism as an Event of Taking Responsibility (Langham Academic, 2022). ISBN: 9781839732348 Mark Valeri, The Opening of the Protestant Mind: How Anglo-American Protestants Embraced Religious Liberty (Oxford University Press, 2023). ISBN: 978-0197663677